Revitalizing Learning Concentration: Exploring Ice-Breaking Techniques to Improve Reading Proficiency in Elementary School - Nurul Aswar; Iramaya Iramaya (Didaktika: Jurnal Kependidikan, 2023)
This research aims to increase students' learning concentration in learning to read in class III elementary schools by applying the ice-breaking technique. This classroom action research was carried out over two cycles. Data was collected through observation, questionnaires, interviews and documentation. The research results show that the use of ice-breaking techniques is effective in increasing students' learning concentration. The questionnaire showed an increase in concentration from "poor" in the initial stage to "very good" in the second cycle. Observations of student activities also showed a significant increase from "poor" to "very good" in the second cycle. This research has important implications in the educational context, namely that teachers can utilize ice-breaking techniques to increase learning effectiveness and create a positive classroom environment. Although there are several limitations to this study, the results provide an important contribution to the educational context and provide a basis for further research.